Enhancing the Visual Experience:Analysis of the performance and challenges of Stereoscopic 3D technology in game design and virtual reality - Lawrence Philip,B.A, M.M, Lawrence Philip,B.A, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2025)
In the era of digital innovation, Stereoscopic 3D (S3D) technology is becoming popular in game design and virtual reality, although it faces challenges related to user convenience. This research aims to analyze the challenges and opportunities associated with the use of S3D, as well as to explore best practices for enhancing the user experience. The method employed is a literature analysis that includes the collection and evaluation of sources related to S3D, game design, and user experience. The findings underscore the significance of selecting suitable stereoscopic parameters, understanding perceptual psychology, and integrating emerging technologies, such as Virtual Reality (VR) and generative AI, to craft immersive and comfortable visual experiences. The research also emphasizes the importance of a collaborative design approach to meeting user expectations and mitigating discomfort experienced during interactions with S3D content.